Xanthagaricus thailandensis sp. nov. (Agaricales, Basidiomycota), from northern Thailand - Kumla, Jaturong; Suwannarach, Nakarin; Sri-Ngernyuang, Kriangsak; Lumyong, Saisamorn (Phytotaxa, 2018)
A new species of agaricomycetes, Xanthagaricus thailandensis, is described based on collections from northern Thailand. This species is characterized by its medium-sized basidiomata, pale orange pileus, a pseudoparenchymatous structure of the squamules on the pileal surface, subcylindrical to clavate caulocystidia and brownish yellow basidiospores. It is clearly distinguished from the previously described Xanthagaricus species by narrow caulocystidia. Molecular phylogenetic analyses, based on a combination of the internal transcribed spacers (ITS) and the large subunit (LSU) of the nuclear ribosomal DNA, also support the finding that X. thailandensis is distinct from other known species within the genus Xanthagaricus. A full description, color photographs, illustrations and a phylogenetic tree showing the position of X. thailandensis are provided.